Detection of some genes encoding pathogenicity factors in the typical isolates of Escherichia coli - E. I. Ivanova; S. M. Popkova; Y. P. Dzhioev; V. V. Dolgikh; E. B. Rakova; E. V. Bukharova (Acta Biomedica Scientifica)
Using polymerase chain reaction 316 strains of E. coli (strains with normal enzymatic activity, strains with weak enzymatic activity and strains with hemolytic activity) were examined for the presence of pathogenicity genes. They were isolatedfrom healthy children and children with functional disorders of the gastro-intestinal tract. The studies have shown that strains of Escherichia coli have pathogenic potential, as evidenced by the presence of genetic pathogenicity markers in them.